pembelajaran tari muli siger menggunakan media audio-visual pada ekstrakurikuler di smk muhammadiyah 1 pringsewu - atika nur tsabita; susi wendhaningsih; hasyimkan hasyimkan (Jurnal Seni dan Pembelajaran, 2019)
Research on the use of audio-visual media and the learning process of muli siger dance in extracurricular activities at SMK Muhammadiyah 1 Pringsewu. This research was conducted to describe the learning process of muli siger dance using audio-visual media. This type of research is descriptive qualitative. The theory used is the theory of constructivism. Data collection techniques were carried out by observation, interviews and documentation. The results of the study there are 6 aspects of the use of audio-visual media, aspect of students observing the muli siger dance video, aspect is the seriousness of students in participating in the learning of muli siger dance, aspect is the activeness of students in asking questions, aspect is understanding the range of motion material in the learning of muli siger dance given by the teacher, aspect is students 'enthusiasm in using media, the sixth aspect is students' ability to utilize learning media. Student learning outcomes in learning muli siger dance get good assessment criteria. Penelitian mengenai penggunaan media audio-visual dan proses pembelajaran tari muli siger pada ekstrakurikuler di SMK Muhammadiyah 1 Pringsewu. Penelitian ini dilakukan untuk mendeskripsikan proses pembelajaran tari muli siger menggunakan media audio-visual. Jenis penelitian ini adalah deskriptif kualitatif. Teori yang digunakan adalah teori konstruktivisme. Teknik pengumpulan data dilakukan dengan observasi, wawancara dan dokumentasi. Hasil penelitian terdapat 6 aspek penggunaan media audio-visual yaitu siswa mengamati video tari muli siger, keseriusan siswa dalam mengikuti pembelajaran tari muli siger, keaktifan siswa dalam bertanya, pemahaman materi ragam gerak pada pembelajaran tari muli siger yang diberikan oleh guru, antusias siswa dalam menggunakan media, aspek keenam kemampuan siswa dalam memanfaatkan media pembelajaran. Hasil belajar siswa dalam pembelajaran tari muli siger mendapat kriteria penilaian baik. Kata kunci: Pembelajaran, Media audio-visual, Tari Muli Siger.